The sustainable intensification concept in agricultural research: normative vs farmers' perspectives - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2022)
Presentation by Dr. Bekele Kotu during IITA Staff Seminar on 1 April 2022.